2010
DOI: 10.1111/j.1365-294x.2010.04849.x
|View full text |Cite
|
Sign up to set email alerts
|

Pollen foraging behaviour of solitary Hawaiian bees revealed through molecular pollen analysis

Abstract: Obtaining quantitative information concerning pollinator behaviour has become a primary objective of pollination studies, but methodological limitations hinder progress towards this goal. Here, we use molecular genetic methods in an ecological context to demonstrate that endemic Hawaiian Hylaeus bees (Hymenoptera: Colletidae) selectively collect pollen from native plant species in Haleakala and Hawaii Volcanoes National Parks. We identified pollen DNA from the crops (internal storage organs) of 21 Hylaeus spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 29 publications
1
59
0
Order By: Relevance
“…Early studies typically relied on either direct Sanger sequencing of purified PCR amplicons (Longhi et al 2009;Wilson et al 2010), for singlespecies barcoding, or else, for multi-species samples, Sanger sequencing of amplicon clones randomly selected from PCR products (Galimberti et al 2014;Bruni et al 2015). The latter has mostly been superseded by HTS approaches for DNA metabarcoding.…”
Section: Component 4: Sequencing Methodologies and Bioinformatics Pipmentioning
confidence: 99%
“…Early studies typically relied on either direct Sanger sequencing of purified PCR amplicons (Longhi et al 2009;Wilson et al 2010), for singlespecies barcoding, or else, for multi-species samples, Sanger sequencing of amplicon clones randomly selected from PCR products (Galimberti et al 2014;Bruni et al 2015). The latter has mostly been superseded by HTS approaches for DNA metabarcoding.…”
Section: Component 4: Sequencing Methodologies and Bioinformatics Pipmentioning
confidence: 99%
“…DNA sequencing has been used successfully to identify the foraging preference of honeybees and the floral composition of their honey (Bruni et al., 2015; De Vere et al., 2017; Galimberti et al., 2014; Hawkins et al., 2015; Jain, Jesus, Marchioro, & AraĂșjo, 2013; Valentini, Miquel, & Taberlet, 2010). Several studies have also used pollen DNA sequencing to identify solitary bee foraging preferences (Sickel et al., 2015; Wilson, Sidhu, Levan, & Holway, 2010). One challenge where DNA may provide a solution is to resolve interactions when the diversity of plants visited is high.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting solution was used as a DNA template for PCR. Wilson et al (2010) found that mixed pollen loads composed of multiple species (as low as 1% w/v) did not yield usable sequence data because the resulting sequences were very short and of low quality. Moreover, honey bees are floral constant and typically return to the hive with pure pollen loads (Grant 1950).…”
Section: Molecular Pollen Identificationmentioning
confidence: 99%
“…Using DNA barcodes to study plant-pollinator interactions DNA barcoding can illuminate the vital ecosystem service provided by bee pollinators (Wilson et al 2010) and help identify which plant species sustain bee populations. Researchers can identify pollen to genera or species using standard PCR and Sanger sequencing techniques, without specialist training or amassing a large library of pollen reference slides.…”
Section: Effect Of Season On the Spatial Distribution Of Pollen Sourcesmentioning
confidence: 99%